2014
DOI: 10.1021/nl5033588
|View full text |Cite
|
Sign up to set email alerts
|

Easy Preparation of Self-Assembled High-Density Buckypaper with Enhanced Mechanical Properties

Abstract: A controlled assembly and alignment of carbon nanotubes (CNTs) in a high-packing density with a scalable way remains challenging. This paper focuses on the preparation of self-assembled and well-aligned CNTs with a densely packed nanostructure in the form of buckypaper via a simple filtration method. The CNT suspension concentration is strongly reflected in the alignment and assembly behavior of CNT buckypaper. We further demonstrated that the horizontally aligned CNT domain gradually increases in size when in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 62 publications
1
56
0
Order By: Relevance
“…For example, Oh et al (2015) reported an easy preparation of CNT networks constructed by slightly curved CNTs ( CNT α o0.6), and in this case, the straight-CNT model and its results are applicable.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Oh et al (2015) reported an easy preparation of CNT networks constructed by slightly curved CNTs ( CNT α o0.6), and in this case, the straight-CNT model and its results are applicable.…”
Section: Discussionmentioning
confidence: 98%
“…It should be noted that researchers are trying to make the CNTs in the networks as straight as possible (Lu and Chen, 2010;Oh et al, 2015;Wang et al, 2010). For example, Oh et al (2015) reported an easy preparation of CNT networks constructed by slightly curved CNTs ( CNT α o0.6), and in this case, the straight-CNT model and its results are applicable.…”
Section: Discussionmentioning
confidence: 99%
“…Another film‐aided assembly method is called the Buckypaper method that the prototype was obtained in the reference above . Oh et al developed a facile approach to align CNTs with a high packing density using a filtration method, and the schematic illustration is shown in Figure . When the suspension passed through the filter paper, the CNTs immediately began to accumulate on the membrane surface under the force of the hydrodynamic drag and formed an ordered deposit with an aligned arrangement.…”
Section: Film‐aided Assemblymentioning
confidence: 99%
“…Many methods can produce large-scale CNT film. For example, suspension-based vacuum filtration method [8][9][10][11], directly drawing method [12][13][14], floating catalyst chemical vapor deposition (FCCVD) method [15], and other methods including hydroentangling [16] and electrochemical chemical deposition [17]. However, the vacuum filtration method could not produce strong films [18].…”
Section: Introductionmentioning
confidence: 99%